Descriptive Analysis of the Incidence of Suicide Due to Sharp Injuries at the Bhayangkara Tk. 1 Pusdokkes Polri Hospital: A Review of Data From the Last Five Years and an Islamic Perspective - Febi Rahma Putri; Farah Primadani Kaurow; Siti Marhamah (Eduvest - Journal of Universal Studies, 2026)
Suicide is one of the leading causes of death and remains a major global public health issue. Although suicide by sharp force is relatively uncommon, it has distinctive forensic characteristics and a high fatality rate. This study aims to describe the incidence and characteristics of suicide cases caused by sharp force injuries handled by Bhayangkara Tk.1 Pusdokkes Polri Hospital during the last five years and to analyze the phenomenon from an Islamic perspective. This was a descriptive retrospective study using secondary data obtained from medical records and forensic autopsy reports at Bhayangkara Tk.1 Pusdokkes Polri Hospital between 2020 and 2024. The analyzed variables included gender, age, religion, occupation, place of incident, type of weapon used, wound characteristics, cause of death, and mechanism of death. Data were presented in frequency distributions and analyzed descriptively. A total of five suicide cases by sharp force were recorded during the study period. All victims were male, with a mean age of 32.4 years, and most were Muslims. The majority were private employees or students. The most commonly used weapon was a knife, and the incidents predominantly occurred at home. Fatal wounds were mostly located on the neck, with clean-cut edges. Internal examination revealed injuries to vital organs such as the lungs, heart, and liver. The primary cause of death was sharp force injury to major blood vessels or vital organs, with the dominant mechanism being hypovolemic shock due to massive hemorrhage.